ANALISIS TES PENILAIAN PENCAPAIAN KOMPETENSI PADA MAHASISWA KEBIDANAN: Array (LPPM STIKes Buleleng, 2020)
An examination test is one method to assess learning outcomes. Item analysis may be used to assess validity and reliability of the test. However, limited analysis is employed in the current practice. This research aims to analyse midwifery students’ competency test. The analysis of Competency assessment tools includes level of difficulties and level of differences. This study was conducted on midwifery students in their fifth semester. The tools consist of 120 items with multiple choice questions. Students’ response was analysed based on level of differences, biseral point and KR-20. Data was reported descriptively. This study showed that 42% items were at easy level, 38% items had low level of differences, and 71% items were invalid. This meant that many items in the tools need to be amended. Reliability test on valid items shows a very good level of reliability, which is 0.892. By carrying out item analysis the expectation will be able to measure actual student competencies. Key words: Competency assesment test , validity, reliability.